(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to analyze the costs associated with antibiotic (AB) at Le Van Thinh Hospital (LVTH) from 2023 to 2024. Methods: A cross-sectional descriptive study was conducted using retrospective data on AB costs for health insurance (HI) patients treated at LVTH between April 2023 and March 2024. AB costs were categorized based on the characteristics of antibiotic groups, including chemical subclassification, components, and country of production. Results: From April 2023 to March 2024, the total cost of antibiotics used for treating HI patients at LVTH was 39.5 billion VND, with inpatient treatments accounting for 66.8% of this total. Beta-lactam antibiotics incurred higher costs than other groups in both outpatient and inpatient settings, accounting for 75.0% and 67.0% of costs, respectively. There was a notable difference in the proportion of frequently used AB groups between inpatient and outpatient treatments. Conclusion: The study observed variations in AB usage demand (increase/decrease) across different quarters within the study period, and between inpatient and outpatient treatments. These findings provide a basis for hospital drug management personnel to adjust procurement and ordering practices in line with actual drug usage trends at the hospital.